PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES BERBANTUAN POWER POINT TERHADAP HASIL BELAJAR SENI RUPA SISWA SMAN 15 PADANG - Dina Febrianti, Dra. Zubaidah, M.Pd. (Universitas Negeri Padang, 2019)
This research aims is to find out whether there is a positive impact from using examples non examples cooperative learning model assisted by power point towards the learning outcomes of students of Padang 15 High School. The research used is type quantitative with quasi experiment approach. All students of class X IIS of Padang 15 High School became population in this study. Then the research used from class X IIS 1 and X IIS 3 as samples using random sampling techniques. This research instrument is student learning outcomes. After Data is obtained, then he data is analyzed using Independent sample t-test. The use of cooperative learning models of examples non examples types assisted by power points differ significantly by using conventional learning models on student learning outcomes.Keywords: Example Non Example, Learning Outcomes